Uji Aktivitas Antibakteri Ekstrak Daun Pepaya (Carica papaya) dan Ekstrak Kunyit Putih (Curcuma zedoaria) Terhadap Escherichia coli dan Staphylococcus epidermidis - Herlina Lumbantobing; Sartini Sartini; Rahmiati Rahmiati (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2022)
This study aims to determine the active ingredients contained in papaya leaf extract (Carica papaya) and white turmeric extract (Curcuma zedoaria) and their antimicrobial activity against Escherichia coli and Staphylococcus epidermidis. This research was conducted using experimental methods at the Laboratory of Molecular Biology, Faculty of Medicine, University of Prima Indonesia. The research data were analyzed using a completely randomized design approach. Papaya leaf extract and white turmeric were made at different concentrations of 25%, 50%, 75% and 100% and the positive control was the antibiotic chloramphenicol (2 g). The results showed that papaya leaf extract contains active compounds of flavonoids, alkaloids, terpenoids and saponins. While white turmeric extract contains flavonoids, steroids, tannins and saponins. Papaya leaf extract 100% is the best treatment to suppress the growth of bacteria Echerichia coli and Staphylococcus epidermidis with an average inhibition of 14,110 mm and 14,707 mm, respectively. The administration of 100% white turmeric extract was the best treatment to suppress the growth of E. coli and S. epidermidis with an average inhibition of 14,307 mm and 13,743 mm, respectively.